Enterprise Content Management (ECM) System Architecture for Capital Project at Oil and Gas Company - Herdiansah, Arief (JISA(Jurnal Informatika dan Sains), 2022)
The Enterprise Content Management System (ECM) is an improvement over the Document Management System (DMS) solution. In a DMS solution, corporate documents will be managed at the document level (access rights and document distribution processes) while in an ECM solution, documents can be managed down to the level of content contained in the document. Companies who are engaged in the oil and gas industries, are facing intense business competition and to be able to win the competition, companies must be able to increase their HSE (Health, Safety, and Environmental) supervision. Document content management systems are needed by companies that have capital projects, including oil and gas companies. Before a company builds and implements an ECM solution to manage project capital documents, it is necessary to build a system design architecture so that the built ECM solution can meet user needs in managing documents down to the content level. ECM is one of the enterprise solutions, so an Enterprise Architecture (EA) scale system design is needed with a focus on Digital Enterprise Architecture (DEA). This research produces a reference in the process of making ECM architecture in order to manage project capital documents in oil and gas companies.